Challenges of South-South Cooperation in the Era of Globalization - Hellandendu, Akaknaya Wesley; Hamidu, Ishaku (Kashere Journal of Politics and International Relations, 2024)
Developing countries are known to be facing multiple interlinked macroeconomic, financial and developmental challenges in this globalized world system. Using secondary data, this paper observed that developing countries have no control over manufacturing, had no tangible development in the area of Information Communication Technology, (ICT), trade services and military technology. Hence, the control of the global economy is left to the dictates of the North. The South-South Cooperation (SSC) is therefore an important mechanism for developing countries to meet these challenges individually and collectively, in multilateral North-South dialogue and global governance. The effectiveness of the South-South Cooperation (SSC) in surmounting these challenges was examined. It highlighted some challenges such as weak institutional set up and framework, insufficient capacity in project management, lack of policy coordination among developing countries as well as inappropriate development strategies as major hindrances of the South-South Cooperation. This paper further identified processes of globalization such as liberalization of trade and finance, finance and investment and the globalization of policy making as some factors that have grave implications on the development of the South. The paper concludes that the SSC should take advantage of the economic crisis between the US and China, and liaise with China in the areas of research and technology transfer. Members of South-South Cooperation are recommended to boosts their economies, balance opportunities and problems resulting from globalization, policy coordination among developing countries, and search for appropriate development strategies.